The Influence of Financial Ratios and Company Size on Bond Ratings of Banking Companies Listed on the Indonesia Stock Exchange in 2019-2024 - Triana, Dinie; Putri, Amelia; Faradhilla, Anatasia; Putri, Alya Nabila (Economic: Journal Economic and Business, 2025)
This study analyzes the influence of financial ratios and firm size on bond ratings of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2024 period. The independent variables include liquidity (Current Ratio), leverage (Debt to Equity Ratio), profitability (Return on Assets), and firm size (Size), with bond ratings as the dependent variable. A quantitative method with ordinal logistic regression is employed to examine the relationships among these variables. Secondary data were obtained from banking companies’ financial reports and bond ratings issued by PT Pefindo. The findings indicate that profitability (ROA) has a significant negative effect on bond ratings, suggesting that highly profitable companies do not necessarily receive better ratings. Meanwhile, leverage (DER), liquidity (CR), and firm size do not significantly impact bond ratings. The regression model is validated with a Nagelkerke R2 value of 0.784, indicating that the independent variables explain 78.4% of the variation in bond ratings. These results provide insights for investors and stakeholders that profitability plays a more critical role in determining bond ratings than other financial factors. Therefore, banking companies should optimize their profitability management to enhance bond credibility in financial markets.